Hypersensitivity of lung vessels to catecholamines in systemic hypertension. Issue 6542 (2nd August 1986) - Guazzi, M D; Alimento, M; Fiorentini, C; Pepi, M; Polese, A
Abstract : Among patients with primary systemic hypertension pressure and arteriolar resistance in the pulmonary circulation exceed normal values and are hyper-reactive to sympathetic stimulation. A study was therefore carried out in 16 patients with uncomplicated essential hypertension and nine healthy subjects to compare the pulmonary vascular reactivity to exogenous catecholamines. In the normotensive group the dose response relation to adrenaline (microgram: dyn) was 1 = -4, 2 = -9, 3 = -9, and 4 = -10 and to noradrenaline 2 = +3, 4 = /8, 6 = +4, and 8 = +3. The relations in the hypertensive subjects were 1 = +18, 2 = +42, 3 = +59, and 4 = +77 and 2 = +39, 4 = +54, 6 = +76, and 8 = +100, respectively. Group differences were highly significant. Cardiac output (blood flow through the lungs) was raised by adrenaline and reduced by noradrenaline. In either case the driving pressure across the lungs was significantly augmented in the hypertensive patients but not in the normotensive group. Both catecholamines had a vasoconstrictor effect on the pulmonary circulation as a result of vascular over-reactivity. The opposite changes in resistance between normal and hypertensive subjects produced by adrenaline suggest that a constrictor vascular hypersensitivity occurs in the pulmonary circulation with the development of systemic high blood pressure.